Density functional study on the geometric features and growing pattern of AlnNm clusters (n = 1-4, m = 1-4, n + m ≤ 5) - Ferraresi Curotto, Verónica (2011)
The bonding features of AlnNm clusters (n = 1–4, m = 1–4, n + m ≤ 5) are studied within the framework of the density functional theory following a systematic growing mechanism. Various geometries are found to be more stable than structures reported elsewhere for small Al–N aggregates. In other cases, good agreement exists with results already reported by other authors. It is also found that Al–N clusters tend to grow mainly towards nonlinear bidimensional structures up to the pentamer. The ability to form triple N–N bonds is important for the relative stability of clusters as they grow. The growing patterns could be explained mainly in terms of electrophilic attacks of both Al and N atoms to the corresponding sites in the aggregates of lower size. It is found that atomic charges derived from molecular electrostatic potentials allow to rationalize the electrophilic attacks, being then useful to understand the growing paths followed by small Al–N clusters.